In vitro Anti‐atherogenic Properties of N‐Heterocyclic Carbene Aurate(I) Compounds. (27th November 2018) - Sioriki, Eleni; Lordan, Ronan; Nahra, Fady; Van Hecke, Kristof; Zabetakis, Ioannis; Nolan, Steven P.
Abstract: The anti‐atherogenic (anti‐inflammatory) properties of various aurate(I) salts, of the general formula [NHC⋅H][AuCl2 ] (NHC=N‐heterocyclic carbene) were investigated. The aurates were easily synthesized and obtained in analytically pure form. In addition, the biological activity of these compounds against atheromatosis via in vitro inhibition of platelet‐activating factor (PAF)‐induced platelet aggregation was probed. All complexes were found to possess anti‐aggregatory properties in vitro with [IPr*⋅H][AuCl2 ] (6 ) being the most potent inhibitor of PAF at micromolar concentration. Based on our findings, we conclude that these simply assembled aurates are a very promising class of PAF inhibitors and anti‐inflammatory drugs. Abstract : Good as gold : A series of N‐heterocyclic carbene (NHC)–aurates were synthesized and evaluated for their anti‐atherogenic properties toward platelet‐activating factor (PAF)‐induced aggregation of human platelet‐rich plasma (PRP). Both the gold and NHC moieties were shown to be crucial for good activity. All complexes were found to possess in vitro anti‐aggregatory properties.